2007
DOI: 10.1111/j.1365-2648.2007.04264.x
|View full text |Cite
|
Sign up to set email alerts
|

Does obesity prevent the needle from reaching muscle in intramuscular injections?

Abstract: Intramuscular injections administered at the dorsogluteal site in 98% of women and 37% of men, and at the ventrogluteal site in 97% of women and 57% of men, would not reach the muscles of the buttock. A needle longer that 1.5 inches should be used in women whose body mass index is more than 24.9 kg/m2, the dorsogluteal site may be used in all overweight and obese men, and the ventrogluteal site may be used in overweight men only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
96
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(106 citation statements)
references
References 8 publications
6
96
0
4
Order By: Relevance
“…2 Similar studies have shown that problems with under-penetration are even more pronounced at the gluteal IM injection sites. 7,8 In a study done in South Korea it was found that boys over 14 years of age had statistically significantly thinner subcutaneous tissue at all injection sites than that of age matched girls. It was also found that body mass index (BMI) was statistically significantly correlated with subcutaneous tissue thickness at all sites.…”
Section: Introductionmentioning
confidence: 99%
“…2 Similar studies have shown that problems with under-penetration are even more pronounced at the gluteal IM injection sites. 7,8 In a study done in South Korea it was found that boys over 14 years of age had statistically significantly thinner subcutaneous tissue at all injection sites than that of age matched girls. It was also found that body mass index (BMI) was statistically significantly correlated with subcutaneous tissue thickness at all sites.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5,30,34] Even though worldwide injection practices are based on these guidelines, there is increasing evidence validating IM injections with a 1.5-inch long needle may not be reaching muscle, especially in females exceeding a BMI of 30. [2,11,35] Additionally, educational texts may vary in their instructional information related to injection practices.…”
Section: Injection Depthmentioning
confidence: 99%
“…Increasing body fat, as measured by BMI in this investigation, was significantly associated with developing an abscess following injection of pf-MPA. Previous studies have identified the need to take into account weight and fat pad depths when administering intramuscular injection, and as such, alter needle length and gauge accordingly [20][21][22]. Although this facility did increase needle length (from 1 inch to 1.5 inches) for patients with BMI greater than 25, the needle length selection was still likely insufficient to reach the intramuscular depth required for injection [22].…”
Section: /6mentioning
confidence: 99%
“…Previous studies have identified the need to take into account weight and fat pad depths when administering intramuscular injection, and as such, alter needle length and gauge accordingly [20][21][22]. Although this facility did increase needle length (from 1 inch to 1.5 inches) for patients with BMI greater than 25, the needle length selection was still likely insufficient to reach the intramuscular depth required for injection [22]. Facilities administering these types of injections should have written protocols for intramuscular injections that account for the increased fat pad of some patients and specify the appropriate needle length and gauge.…”
Section: /6mentioning
confidence: 99%